VM placement and cache based side channel attack at computational level in cloud computing : A Survey. (4th July 2021) - Hansraj,; Tiwari, Pradeep Kumar; Chaudhary, Alka
Abstract: There are different issues that need to focus in respect of security and privacy. One of the most security issue at computational level implementation of secure virtualization is cloud computing. In this, we explain virtualization security and their existing defense system at computational level. In computational level need to increase security of cloud and categorized the virtual machine level security challenges that are faced by cloud users at computational level in cloud computing. Day by day cloud attribute are introducing new challenges in cloud environment. In this paper, we focus on cloud security at computational level. In the day scenario to secure a cloud data on shared environment is the important task for IT industries. In virtual environment need to focus on secure VM placement on the host machine that is running on cloud. This paper demonstrates lack of VM placement and side channel attack (SCA). Analysis of different type of scheme is done and comparative study of game theory based, graph theory based and bin packing VM placement scheme. Also we discussed virtualization in cloud computing and their security aspects and comparative study of different type side channel attack (SCA).